Preparation of N-acetyl-D-glucosamine and N,N-diacetylchitobiose by enzymatic hydrolysis of squid pen chitin - Thitima Maneekul (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2006